2014
DOI: 10.5751/es-06243-190231
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reciprocal connections between demographic decision making and land use on decadal dynamics of population and land-use change

Abstract: The effect of reciprocal connections between demographic decision making and land use on decadal dynamics of population and land-use change. Ecology and Society 19(2): 31. http://dx.doi.org/10.5751/ ES-06243-190231 Research, part of a Special Feature on Exploring Feedbacks in Coupled Human and Natural Systems (CHANS) ABSTRACT. Although much focus has been given to the study of land use and land cover (LULC) and population change, studies have tended to focus on relationships in a single direction, for insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In recent years, ABM has increasingly been used in these ways to enhance our understanding of coupled human and natural systems, complexity theory, human decision-making, cooperation, and demographic and socioeconomic influences on behavior (see e.g., An et al, 2005;An et al, 2006;. systems (see e.g., Berger, 2005;, forest management scenarios Villino, 2014), socio-demographic variables in Nepal Zvoleff & An, 2014), the effects of perceptions and decision making in coupled human and natural systems , and the effects of individual cooperation and interaction on LULCC (see e.g., Zvoleff & An, 2014).…”
Section: Epstein's 1999 Paper Agent-based Computational Models and Gmentioning
confidence: 99%
“…In recent years, ABM has increasingly been used in these ways to enhance our understanding of coupled human and natural systems, complexity theory, human decision-making, cooperation, and demographic and socioeconomic influences on behavior (see e.g., An et al, 2005;An et al, 2006;. systems (see e.g., Berger, 2005;, forest management scenarios Villino, 2014), socio-demographic variables in Nepal Zvoleff & An, 2014), the effects of perceptions and decision making in coupled human and natural systems , and the effects of individual cooperation and interaction on LULCC (see e.g., Zvoleff & An, 2014).…”
Section: Epstein's 1999 Paper Agent-based Computational Models and Gmentioning
confidence: 99%
“…This type of negative agricultural feedback is not always manifested as a management measure because it could also be spurred by individual agents themselves if they change their own behavior in response to availability of agricultural resources. This occurred in Zvoleff and An (2014) in which households living in economically poor rural areas faced complex choices about how to maximize livelihoods. The authors found that households living in agricultural areas tended to delay marriage to maximize their opportunity to gain income via farming, an effect that decreased population growth and thus changed agricultural production over the long term.…”
Section: Overview Of Chans Feedbacks Across Landscapesmentioning
confidence: 99%
“…Long time lags give rise to loose feedbacks and short time lags to tight feedbacks. For example, Zvoleff and An (2014) found that the feedback created from changing the timing of first birth of offspring in the household on land use was a loose feedback that did not emerge for several decades, probably because of the generation time required for offspring to mature. In this case, the feedback would not have been detected if the authors had limited their research to a shorter time frame.…”
Section: Time Lagsmentioning
confidence: 99%
“…Land 2017, 6, 29 3 of 23 ecosystem services received by society [26,27]. Understanding the objectives and connected decisions behind varying management practices is an essential part of placing this research within a CHANS framework [28,29].…”
Section: Study Areamentioning
confidence: 99%